Análisis financiero integral y estudio del capítal de trabajo a la entidad económica Almacén Peñaloza del Cantón Huaquillas, para los períodos 2011-2012 - Abalo Nabarro, Victor Mauricio (2016)
The thesis work whose theme is, "Comprehensive Financial Analysis and Study of Working Capital to the economic entity store Peñaloza Canton Huaquillas for the periods 2011 - 2012", was developed in the framework of a comprehensive review of the financial statements through the application of different methods and analysis techniques, as well as the respective quantitative interpretation of these data. On the other hand the study of the major accounts that make up working capital, carefully examining their behavior and levels of investment in the financial structure of the business is conducted. In the parameters or targets summed up in a close-up analysis of the financial and economic situation, through the implementation of comprehensive financial statements for each of the years of vertical percentages, the increases and decreases also established product accounts of business operations between 2011 and 2012. Applying corroborated trends indicate high propensity, constants and low fluctuations in the various screeds of financial reports, allowing analyzing patterns of behavior and the reasons that caused them. The calculation of financial the ratios possible to measure and compare the levels of liquidity, profitability and debt providing information relevant to the administration of the company, the Dupont system where it was found that the yield obtained comes mainly from its assets , the Economic Value Added (EVA ) identified the degree of added value once managed to cover the opportunity costs of the owner of the company , the Balance Point contrasted the revenue generated by sales, expenses and cost of sales , on a point of equality where the flow of operations is a zero , ie no gain or loss is acquired. In working capital proportionality and variation that has been in the periods in his studied, independent analysis of its components such as Cash, Accounts Receivable and Inventory of Goods fully examined in relation to the field was analyzed administrative company. Finally the report that collects and provides the results was done, reflecting the economic and financial performance of the company. Methodological parameters used for the development of this thesis are the following methods: scientific, inductive, analytic and synthetic, also some research techniques was used as interview, observation and bibliography that played a major role in inquiry and studied in the framework proposed topic. In conclusion, results of this study and analysis could determine that reach liquidity levels have decreased since the Acid Test earned $ 1.3 for 2011 and $ 0.55 in 2012 , a result that did not help solve their short-term debts , which were affected by the lack of a financial analysis and inadequate management decisions , which have to do with excessive purchases of goods by the over-estimation of sales, leaving the effect of accumulation capital assets and low levels of liquidity for the current period also by higher payments to suppliers. To which the manager - owner recommends applying appropriate as financial planning measures where conduct a study of economic change on the local market, prioritizing stock items wholesale and retail, thus optimizing liquid assets within the financial structure company .